Relationship of knee extension strength and anthropometric variables to alpine ski racing success - Crockett, B. A.; Jensen, R. L. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: A large amount of knee extensor strength is often cited as a requirement for alpine ski racing success. Takashi et al. (1992) found that eccentric knee extension and flexion strength may be related to racing success in national caliber athletes. In contrast, Neumayr et al. (2003) found no correlation between muscle strength and racing performance in world class athletes. Few studies have examined these types of relationships in recreational athletes. The current study examined the relationship of isometric strength of the knee extensors and anthropometric measures to success in recreational alpine ski racing.